General Review on Malaysian Standard Forms of Construction Contracts - Ting, S.; Whyte, Andrew (University Sains Malaysia, 2009)
In Malaysia, general conditions of contract are compiled as a set of documents commonly known as the standard forms of contract. With the perceived advantages and the assumed need for familiarity, the standard forms have been deemed as the best way to go in Malaysian contracting despite its shortcomings. This paper summarizes and reviews of the common and most popular construction standard forms of contract currently in used in Malaysia. Forms reviewed are the Pertubuhan Arkitek Malaysia (PAM) forms, Public Works Department (PWD) forms, Construction Industry Development Board (CIDB) forms and Institution of Engineers, Malaysia (IEM) forms. It is seen that Malaysian contract forms used in construction in the matters of numbers, coverage of issues, lacks clarity, comprehensiveness and completeness, lack of international efficiencies and the mentality of stakeholders when it comes to form selection, which will greatly affect good project management in terms of contract administration.